2020
DOI: 10.1016/j.wneu.2020.05.237
|View full text |Cite
|
Sign up to set email alerts
|

Nasoseptal Flap Necrosis After Endoscopic Skull Base Surgery in the Setting of COVID-19 Pandemic

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Limb ataxia was reported in around 11% of the cases including the case reported by one of the authors of the present review. Other less reported neurological symptoms include tonic clonic seizures, slurred speech, [Panariello et al 2020, Yin et al 2020, McAbee et al 2020, Ye et al 2020, Duong et al 2020, Mukhergee et al 2020] Haemorrhagic-Frontal EDH [Al-olama et al 2020] Ischemic-Right caudate nucleus [Morassi et al 2020] Chronic microvascular change [Sohal and Mossamat 2020] 2 MRI NAD- [ref-Chaumont et al 2020, Karimi et al 2020, Dogan et al 2020, Bernard-Valnet et al 2020] T 2 [Wong et al 2020,Afshar et al 2020, Efe et al 2020 or T 2 /FLAIR hyperintensity- [ref-Efe et al 2020, Moriguchi et al 2020, Morassi et al 2020, Ramero-Sanchez et al 2020] Encephalitis like feature (hyperintensity, enhancement, haemorrhage) [Dogan et al 2020 (case nos 1, 2, 6)] DWI Restriction/ADC hypodensity [Moriguchi et al 2020, Hayashi et al 2020 Angiography CTA Beaded appearance- [Al-aloma et al 2020] MRA NA 5 MRS Choline peak- [Efe et al 2020] 4 Not available [Pilotto et al 2020, Packwood et al 2020, Chacon-Aguillar 2020, Talmor et al 2020, Romrero-Sanchez et al 2020, Varatharaj et al 2020 and cognitive difficulties such as verbal and motor perseveration. SARS-CoV-2 detection in CSF was reported in only 3 cases, whereas majority (92.6%) of the patients were diagnosed based on nasopharyngeal swab/oropharyngeal swab/bronchoalveolar lavage testing.…”
Section: Discussionmentioning
confidence: 99%
“…Limb ataxia was reported in around 11% of the cases including the case reported by one of the authors of the present review. Other less reported neurological symptoms include tonic clonic seizures, slurred speech, [Panariello et al 2020, Yin et al 2020, McAbee et al 2020, Ye et al 2020, Duong et al 2020, Mukhergee et al 2020] Haemorrhagic-Frontal EDH [Al-olama et al 2020] Ischemic-Right caudate nucleus [Morassi et al 2020] Chronic microvascular change [Sohal and Mossamat 2020] 2 MRI NAD- [ref-Chaumont et al 2020, Karimi et al 2020, Dogan et al 2020, Bernard-Valnet et al 2020] T 2 [Wong et al 2020,Afshar et al 2020, Efe et al 2020 or T 2 /FLAIR hyperintensity- [ref-Efe et al 2020, Moriguchi et al 2020, Morassi et al 2020, Ramero-Sanchez et al 2020] Encephalitis like feature (hyperintensity, enhancement, haemorrhage) [Dogan et al 2020 (case nos 1, 2, 6)] DWI Restriction/ADC hypodensity [Moriguchi et al 2020, Hayashi et al 2020 Angiography CTA Beaded appearance- [Al-aloma et al 2020] MRA NA 5 MRS Choline peak- [Efe et al 2020] 4 Not available [Pilotto et al 2020, Packwood et al 2020, Chacon-Aguillar 2020, Talmor et al 2020, Romrero-Sanchez et al 2020, Varatharaj et al 2020 and cognitive difficulties such as verbal and motor perseveration. SARS-CoV-2 detection in CSF was reported in only 3 cases, whereas majority (92.6%) of the patients were diagnosed based on nasopharyngeal swab/oropharyngeal swab/bronchoalveolar lavage testing.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Clinically, Inouye et al 2 reported free flap failure in patients with SARS-CoV-2, and Talmor et al . 20 described pedicled nasoseptal flap necrosis and failure due to SARS-CoV-2 infection. A systematic review by Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Combining this with the predilection of SARS-CoV-2 to cause microvascular pathology suggests that free-flap reconstructions may face unique challenges with concurrent SARS-CoV-2 infection. Several case studies have described remarkable surgical site complications in the setting of SARS-CoV-2 infection [13][14][15]. Benmoussa et al described the failure of a chimeric thoracodorsal artery perforator flap and a free fibula flap performed for gingival mandibular squamous cell carcinoma, and da Silveira et al describe significant sternal dehiscence following a coronary artery bypass graft [14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies are limited by the unknown timeline for SARS-CoV-2 infection. One such study by Talmor et al described a case of pedicled nasoseptal flap necrosis and failure with a positive postoperative SARS-CoV-2 test [ 13 ]. To our knowledge, we are the first to describe near-total STSG loss with severe infectious sequelae in both the donor and recipient sites in major free tissue transfer in the setting of postoperative SARS-CoV-2 infection for patients with negative preoperative testing.…”
Section: Discussionmentioning
confidence: 99%